IMPLEMENTASI PENDIDIKAN TAUHID PADA ANAK DI MADRASAH DINIYAH MUHAMMADIYAH PIJERAN SIMAN PONOROGO - Agus Saikoni; Katni; Anip dwi Saputro (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Tawhid is the initial foundation for a Muslim in his life in the world and in the afterlife. Of course this must be instilled in every Muslim since he was born into the world. Therefore, in addition to formal learning. Education of monotheism in madrasah diniyah muhamadiyah Siman Ponorogo panceran seek through the preliminary prayer time and recite after maghrib and dawn.The objectives of the research are (1) To know the implementation of tauhid education in children in Madrasah Diniyah Muhammadiyah Pijeran Siman Ponorogo, (2) To know monitoring and evaluation of tauhid education in children In Madrasah Diniyah Muhammadiyah Pijeran, Siman, Ponorogo.The approach of this research is qualitative. Techniques of collecting data through interviews, observation, and documentation. Data analysis using descriptive analysis technique, with data reduction flow, display data, and the conclusion of verification, and the thinking model used is inductive.Based on the discussion that has been done previous chapters on Implementation of tauhid education in Madrasah Diniyah Muhammadiyah Pijeran can be drawn conclusion:(1) Implementation of tauhid education applied in Madrasah Diniyah. Muhammadiyah Pijeran is as follows: With the method of memorizing asmaul husna with kinestetik memorize the body movements, hands, feet, natural tadabur that is by inviting students to study in the free to contemplate the creation of Allah SWT. The result of the two methods above is the change of character on the students / santriwati, the prayer becomes more orderly and the students / santriwati increasingly believe in the existence of God so that increasingly its faith. (2) Monitoring and evaluation of education at Madrasah Diniyah Muhammadiyah Pijeran monitoring students by giving control card of prayer and control card to discipline santri then evaluation of tauhid education with periodic system ie uts and uas by inserting tawhid materials in all lessons as for evaluation form can be in the form of written exam and oral examination